Rapid cement stabilized macadam and preparation method thereof

By adopting the compounding technology of an inorganic cementitious material system in cement-stabilized gravel, the hydration reaction time is extended and the cement hydration shrinkage is compensated by the micro-expansion characteristics of magnesium oxide, the problem of cement-stabilized gravel cracking and slow early strength formation is solved, and the effect of high-strength and rapid open traffic is achieved.

CN119874309APending Publication Date: 2025-04-25NANJING XINGYOU TRANSPORTATION TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411862223.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Cement-stabilized gravel is prone to dry and temper-shrinkage cracks under the action of cement hydration reaction, resulting in transverse cracks in the base layer, affecting the stability and service life of the road surface layer. At the same time, the early strength of cement stabilized gravel is slow, resulting in traffic congestion.

Method used

The inorganic cementitious material system is adopted, including ordinary silicate cement, magnesium oxide, metakaolin, retarder sodium dihydrogen phosphate and early strength agent magnesium hydroxide. The hydration reaction time is extended through compounding technology, providing sufficient construction operation time, and compensating cement hydration and shrinkage through the micro-expansion characteristics of magnesium oxide to improve early strength.

Benefits of technology

It effectively solved the problem of cement stabilizing gravel cracking, improved early strength, shortened initial and final setting times, achieved rapid opening of traffic, and at the same time had sufficient construction operation time, solving the contradiction between slow setting and early strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193462670000031
    Figure BDA0005193462670000031
  • Figure BDA0005193462670000041
    Figure BDA0005193462670000041
  • Figure BDA0005193462670000042
    Figure BDA0005193462670000042
Patent Text Reader

Abstract

The invention discloses rapid cement stabilized macadam and a preparation method thereof. The rapid cement stabilized macadam comprises an inorganic cementing material, aggregate and water, the inorganic cementing material comprises a main material, a water reducing agent, a retarder sodium dihydrogen phosphate and an early strength agent magnesium hydroxide; the main materials comprise ordinary Portland cement, magnesium oxide and metakaolin. The preparation method comprises the following steps: mixing the main material, the water reducing agent, the sodium dihydrogen phosphate as the retarder and the magnesium hydroxide as the early strength agent to prepare the inorganic cementing material; and stirring and mixing the inorganic cementing material and the aggregate, adding water, uniformly stirring, and paving, rolling and forming to obtain the rapid cement stabilized macadam. According to the rapid cement stabilized macadam, the problem of cracking of the cement stabilized macadam can be effectively solved, the early strength can be rapidly improved, meanwhile, enough construction operation time is achieved, and the contradiction between delayed coagulation and early strength is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to rapid cement-stabilized crushed stone and a preparation method thereof. Background Art

[0002] The road pavement structure is generally composed of a surface layer, a base layer and a cushion layer. Compared with other base structures, cement-stabilized crushed stone has the advantages of high strength, strong integrity and good durability. After it is cured, it will not become muddy when it rains and has a solid surface. It is an ideal semi-rigid base material and one of the most commonly used base materials for highway pavements, especially high-grade pavements.

[0003] However, in the cement-stabilized gravel base material used in the base layer, the gravel is very likely to form shrinkage and temperature shrinkage cracks under the action of cement hydration reaction. In addition, the road is a strip structure, which makes it easier to cause transverse cracks in the base layer. Under the action of wheel load, the cracks are transmitted to the asphalt concrete structure layer above, resulting in serious "reflective cracks" in the road surface layer, causing road surface damage, and structural repair measures have to be taken. In order to ensure sufficient bearing capacity, the early strength of the cement-stabilized gravel base layer is slow to form, and it takes at least 7 days of maintenance before the surface layer construction can be carried out. However, with the increase in traffic volume, excessive maintenance time is prone to cause traffic jams. Rapidly improving the early strength of cement-stabilized gravel and realizing rapid opening of traffic is one of the effective means to solve the above dilemma.

[0004] Based on this, a method of rapidly improving cement-stabilized crushed stone is now studied, which can rapidly improve early strength and at the same time has sufficient construction operation time to resolve the contradiction between slow setting and early strength. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a fast cement-stabilized gravel, which can not only effectively solve the problem of cracking of cement-stabilized gravel, but also can quickly improve the early strength and at the same time have sufficient construction operation time, solving the contradiction between slow setting and early strength.

[0006] Technical solution: The fast cement-stabilized crushed stone of the present invention comprises, by weight, 4-6 parts of inorganic cementitious material, 89-94 parts of aggregate and 2-4 parts of water;

[0007] The inorganic gelling material comprises a main material, a water reducing agent accounting for 0.35-0.55% of the main material weight, a retarder sodium dihydrogen phosphate accounting for 2.5-4.5% of the main material weight, and an early strength agent magnesium hydroxide accounting for 1.5-2.5% of the main material weight; the main material comprises 60-70 parts of ordinary Portland cement and a specific surface area of ​​100-200 kg / m 2 15-20 parts of magnesium oxide and 10-15 parts of metakaolin.

[0008] The present invention is based on ordinary Portland cement and metakaolin, and uses sodium dihydrogen phosphate as a retarder, and simultaneously compounding magnesium oxide and an early strength agent magnesium hydroxide. Under the condition of a small amount of water to form a semi-dry type and low specific surface area magnesium oxide, the retarder sodium dihydrogen phosphate can be dissolved in water, and the time for the ionization of hydrogen ions in water is increased, and the non-contact and non-reaction time of the ionized hydrogen ions with both magnesium hydroxide and magnesium oxide is prolonged, and then the hydration of ordinary Portland cement is delayed based on the existence of the charged ions, providing time for construction, and playing a sufficient retarding effect. And then when magnesium oxide and the early strength agent contact hydrogen ions, they will dissolve to generate magnesium ions, and react with phosphate ions in the retarder to form a phosphate complex hydrated gel, and gradually increase the pH in the solution, enhance the alkalinity, and stimulate the cement and metakaolin to react. That is, in the system of the present invention, the reaction of magnesium hydroxide and sodium dihydrogen phosphate can be carried out step by step, and the time of the two steps is prolonged, so as to solve the contradiction between retarding and early strength.

[0009] Furthermore, the aggregate used in the present invention is prepared by mixing asphalt concrete milling material or limestone with ceramsite in a ratio of 10: (0.5-1).

[0010] Furthermore, the ceramsite used in the present invention is sludge or steel slag ceramsite, with a particle size of 4.5-9 mm and a bulk density of 1000-1400 kg / m 3 , cylinder pressure strength is greater than 6MPa.

[0011] Furthermore, the asphalt concrete milling material or limestone used in the present invention has different grading compositions: the percentage passing through the 31.5 mm sieve hole is 100%, the percentage passing through the 26.5 mm sieve hole is 90-100%, the percentage passing through the 19 mm sieve hole is 75-85%, the percentage passing through the 9.5 mm sieve hole is 47-59%, the percentage passing through the 4.75 mm sieve hole is 29-40%, the percentage passing through the 2.36 mm sieve hole is 17-27%, the percentage passing through the 0.6 mm sieve hole is 8-16%, and the percentage passing through the 0.075 mm sieve hole is 2-5%.

[0012] Furthermore, the ordinary Portland cement used in the present invention is grade 42.5 or 52.5, and the specific surface area of ​​metakaolin is ≥400kg / m 2 .

[0013] Furthermore, the magnesium oxide used in the present invention is light-burned magnesium oxide, and the water reducing agent is a polycarboxylic acid powder with a water reducing rate of ≥40%.

[0014] The method for preparing the above-mentioned rapid cement-stabilized crushed stone of the present invention comprises the following steps:

[0015] (1) mixing the main material, a water reducing agent, a retarder, sodium dihydrogen phosphate, and an early strength agent, magnesium hydroxide for 3-5 minutes to prepare an inorganic gelling material;

[0016] (2) Stir the above inorganic cementitious material and aggregate for 3-5 minutes, add water and stir evenly, then spread and roll to form fast cement-stabilized gravel.

[0017] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1) The present invention adopts the alkalinity of the early strength agent to stimulate the activity of ordinary silicate cement and metakaolin, so that not only the early strength is guaranteed, but also the later strength can be steadily increased by relying on the hydration of silicate cement. At the same time, the micro-expansion characteristics of magnesium oxide hydration are utilized to compensate for the shrinkage of cement hydration, effectively solving the problem of cracking of cement-stabilized crushed stone; 2) The compounding technology of retarder, magnesium oxide and early strength agent solves the contradiction between slow setting and early strength of inorganic cementitious material system, so that there is sufficient construction operation time, and the initial setting and final setting time can be quickly shortened, and the early strength of cement-stabilized crushed stone is improved, thereby realizing rapid opening of traffic; 3) The dense and porous internal structure of ceramsite is utilized to provide tiny capillary channels for the penetration movement of water, provide water for the hydration of cement, and reduce the shrinkage and cracking of cement; 4) Aggregates are composed of different graded particle sizes, so that the mixed aggregates have the tightest particle size distribution, thereby also improving the strength and crack resistance of cement-stabilized crushed stone; 5) Milling material can be used as aggregate, so as to achieve comprehensive utilization of waste and meet environmental protection requirements. DETAILED DESCRIPTION

[0018] The technical solution of the present invention is further described in detail below in conjunction with embodiments.

[0019] It should be noted that the aggregate used in the present invention can be a compound of asphalt concrete milling material and ceramsite at a ratio of 10: (0.5-1), or a compound of limestone and ceramsite at a ratio of 10: (0.5-1). There is no difference in the technical effect of using the two as aggregates. The asphalt concrete milling material or limestone is composed of different gradations: the percentage passing through the 31.5mm sieve hole is 100%, the percentage passing through the 26.5mm sieve hole is 90-100%, the percentage passing through the 19mm sieve hole is 75-85%, the percentage passing through the 9.5mm sieve hole is 47-59%, the percentage passing through the 4.75mm sieve hole is 29-40%, the percentage passing through the 2.36mm sieve hole is 17-27%, the percentage passing through the 0.6mm sieve hole is 8-16%, and the percentage passing through the 0.075mm sieve hole is 2-5%. The ceramsite is sludge or steel slag ceramsite, with a particle size of 4.5-9mm and a bulk density of 1000-1400kg / m 3 , cylinder pressure strength is greater than 6MPa. The specific surface area of ​​the magnesium oxide used is 100-200kg / m 2 .

[0020] The ordinary Portland cement used in the present invention is grade 42.5 or 52.5, and the specific surface area of ​​metakaolin is ≥400kg / m 2 The magnesium oxide is light-burned magnesium oxide, and the water reducing agent is polycarboxylic acid powder with a water reducing rate of ≥40%.

[0021] Example 1

[0022] The component contents of the inorganic cementitious material in Example 1 are shown in Table 1 below, and the component contents of the rapid cement-stabilized crushed stone are shown in Table 2 below.

[0023] Table 1 Component contents of the inorganic gelling material of Example 1 (1 part = 1 kg)

[0024]

[0025]

[0026] Table 2 Component contents of the fast cement stabilized macadam of Example 1

[0027]

[0028] The method for preparing the rapid cement-stabilized crushed stone of Example 1 comprises the following steps:

[0029] (1) mixing the main material, a water reducing agent, a retarder, sodium dihydrogen phosphate, and an early strength agent, magnesium hydroxide for 3-5 minutes to prepare an inorganic gelling material;

[0030] (2) Stir the above inorganic cementitious material and aggregate for 3-5 minutes, add water and stir evenly, then spread and roll to form fast cement-stabilized gravel.

[0031] Example 2

[0032] The component contents of the inorganic cementitious material in Example 2 are shown in Table 3 below, and the component contents of the rapid cement-stabilized gravel are shown in Table 4 below.

[0033] Table 3 Component contents of the inorganic gelling material of Example 2 (1 part = 1 kg)

[0034]

[0035] Table 4 Component contents of the fast cement stabilized macadam of Example 2

[0036]

[0037]

[0038] The preparation method of the rapid cement-stabilized crushed stone in Example 2 is the same as that in Example 1.

[0039] Example 3

[0040] The component contents of the inorganic cementitious material in Example 3 are shown in Table 5 below, and the component contents of the rapid cement-stabilized gravel are shown in Table 6 below.

[0041] Table 5 Component contents of the inorganic gelling material of Example 3 (1 part = 1 kg)

[0042]

[0043] Table 6 Component contents of the fast cement stabilized macadam of Example 3

[0044]

[0045] The preparation method of the rapid cement-stabilized gravel in Example 3 is the same as that in Example 1.

[0046] Comparative Example 1

[0047] The component contents of the inorganic cementitious material of Comparative Example 1 are shown in Table 7 below, and the component contents of the rapid cement-stabilized gravel are shown in Table 8 below.

[0048] Table 7 Component contents of the inorganic gelling material of Comparative Example 1 (1 part = 1 kg)

[0049]

[0050]

[0051] Table 8 Component contents of the rapid cement stabilized gravel of Comparative Example 1

[0052]

[0053] The preparation method of Comparative Example 1 is the same as that of Example 1.

[0054] Comparative Example 2

[0055] The basic steps are the same as in Example 1, except for the amount of water added, as shown in Table 9 below.

[0056] Table 9 Component contents of the rapid cement stabilized gravel of Comparative Example 1

[0057]

[0058] The performance of the fast cement-stabilized crushed stones prepared in the above-mentioned Examples 1 to 3, and Comparative Examples 1 and 2 was tested, and the results obtained are shown in Table 10 below.

[0059] Table 10 Mechanical properties of fast cement stabilized gravel of Examples 1 to 3, Comparative Example 1 and Comparative Example 2

[0060]

[0061] It can be seen from Table 1 that the setting time of the fast cement-stabilized macadam of the present invention can reach 1.5-2.5h, which reserves sufficient construction operation time, and at the same time, the early strength after curing for 1 day can reach more than 4.2MPa, which improves the early strength and has sufficient construction operation time, solving the contradiction between slow setting and early strength. In addition, it can be seen from the 7d splitting strength and 7d shrinkage strain performance of Examples 1 to 3 in Table 10 that the fast cement-stabilized macadam effectively solves the problem of cracking of cement-stabilized macadam.

Claims

1. A fast cement-stabilized gravel, characterized in that: The fast cement-stabilized crushed stone comprises 4-6 parts of inorganic cementitious material, 89-94 parts of aggregate and 2-4 parts of water by weight; The inorganic gelling material comprises a main material, a water reducing agent accounting for 0.35-0.55% of the main material by mass, a retarder sodium dihydrogen phosphate accounting for 2.5-4.5% of the main material by mass, and an early strength agent magnesium hydroxide accounting for 1.5-2.5% of the main material by mass; the main material comprises 60-70 parts of ordinary Portland cement and a specific surface area of ​​100-200 kg / m 2 15-20 parts of magnesium oxide and 10-15 parts of metakaolin.

2. The rapid cement-stabilized macadam according to claim 1, characterized in that: The aggregate is prepared by mixing asphalt concrete milling material or limestone with ceramsite in a ratio of 10: (0.5-1).

3. The rapid cement-stabilized macadam according to claim 2, characterized in that: The ceramsite is sludge or steel slag ceramsite with a particle size of 4.5-9mm and a bulk density of 1000-1400kg / m 3 , cylinder pressure strength is greater than 6MPa.

4. The rapid cement-stabilized macadam according to claim 2, characterized in that: The asphalt concrete milling material or limestone has different grading compositions: the percentage passing through the 31.5 mm sieve hole is 100%, the percentage passing through the 26.5 mm sieve hole is 90-100%, the percentage passing through the 19 mm sieve hole is 75-85%, the percentage passing through the 9.5 mm sieve hole is 47-59%, the percentage passing through the 4.75 mm sieve hole is 29-40%, the percentage passing through the 2.36 mm sieve hole is 17-27%, the percentage passing through the 0.6 mm sieve hole is 8-16%, and the percentage passing through the 0.075 mm sieve hole is 2-5%.

5. The rapid cement-stabilized macadam according to claim 1, characterized in that: The ordinary Portland cement is grade 42.5 or 52.5, and the specific surface area of ​​metakaolin is ≥ 400kg / m 2 .

6. The rapid cement-stabilized macadam according to claim 1, characterized in that: The magnesium oxide is light-burned magnesium oxide, and the water reducing agent is polycarboxylic acid powder with a water reducing rate of ≥40%.

7. A method for preparing the rapid cement-stabilized crushed stone according to claim 2, characterized in that: The steps include: (1) mixing the main material, a water reducing agent, a retarder, sodium dihydrogen phosphate, and an early strength agent, magnesium hydroxide for 3-5 minutes to prepare an inorganic gelling material; (2) Stir the above inorganic cementitious material and aggregate for 3-5 minutes, add water and stir evenly, then spread and roll to form fast cement-stabilized gravel.